PEMBERLAKUAN ASAS KELAYAKAN DAN KEPATUTAN (ASAS EX AEQUO ET BONO) SEBAGAI UPAYA PENGENYAMPINGAN HUKUMAN PIDANA TERHADAP LANSIA - Irvan Suherry; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Elderly or Elderly is someone who, even though he is said to be old, still has rights and obligations.So that the elderly are also included as subjects of criminal law. An elderly person is not impossible tocommit a criminal act. Many elderly people have reported that those who commit criminal acts are anelderly person.And as a legal subject who fulfills the requirements to be held accountable for crimes, an elderlyperson must be held accountable for criminal acts. By looking at the physical and mental condition of anelderly person, it is difficult for the law to provide fair punishment.Because the imposition of a criminal offense is not merely revenge for an act that has been violated,but rather an attempt to provide guidance to the perpetrator of a crime. It becomes very difficult if anelderly person who is old and in poor condition must undergo a process of punishment that takes not a littletime and the mental stresses are there. In the punishment of law enforcement officials in this case the police,prosecutors, judges are important.Keywords: Elderly, Criminal Objectives, Role of Law Enforcement Officials